Implementation Issues of Total Quality Management in Higher Education - Chaudhuri, Debaprayag; Ghosh, Sadhan Kumar (Prabandhan: Indian Journal of Management, 2010)
Quality has become one of the most important competitive strategic tools, and many organizations have realized that it is a key for developing products and services that support continuing success. Quality systems are designed to set a clear direction for organizations to follow; enabling understanding and involvement of employees proceeding towards a common goal.